Incident factors in the volume exported by the port of Esmeraldas period 2012 - 2018 - Alencastro Guerrero, Paúl; Intriago Ferrin, Ana; Calderón Bastidas, Héctor; Quiñonez Cabeza, Manuel (mktDESCUBRE, 2019)
The objective of this article is to analyze the cargo mobilized by the Port of Esmeraldas to export, in order to find the factors that generated the negative variations found between the period 2012-2018. The relevance of this analysis starts on the fact that the volume of cargo exported is one of the main indicators considered when assessing the economic situation of a country, therefore, when identifying counterproductive figures with economic growth, it is necessary that its causes be identified to provide information to the relevant authorities. The quantitative method was applied with an exploratory and descriptive approach, using the survey and the interview as tools to obtain direct information from the clients that export through this port. The results show that the most influential factors correspond to external factor, out of the responsibility of the port, specifically the International Economic and Commercial Situation surrounding the country's export production, especially international prices and the international commercial situation of customers abroad. . Although there were internal operational failures in the port during the same period, from the perspective of the exporting client these were not representative as much as the external reasons found.